High-quality factor Ta2O5-on-insulator resonators with ultimate thermal stability - Bankwitz, Julian Rasmus; Wolff, Martin A.; Abazi, Adrian S.; Piel, Pierre-Maurice; Jin, Lin; Pernice, Wolfram; Wurstbauer, Ursula; Schuck, Carsten (Optics letters, 2023)
Experiments in photonics, laser optics, and quantum technology require low-loss, thermal, and mechanical stability. While photonic integrated circuits on monolithic chips achieve interferometric stability, important nanophotonic material systems suffer from propagation loss, thermal drift, and noise that prevent, for example, precise frequency stabilization of resonators. Here we show that tantalum pentoxide (Ta2O5) on insulator micro-ring resonators combine quality factors beyond 1.8 Mio with vanishing temperature-dependent wavelength shift in a relevant 70 K to 90 K temperature range. Our Ta2O5-on-SiO2 devices will thus enable athermal operation at liquid nitrogen temperatures, paving the way for ultra-stable low-cost resonators, as desired for wavelength division multiplexing, on chip frequency stabilization and low-noise optical frequency comb generation.
Im Text ist "2" und "5" tiefgestellt
Gesehen am 11.03.2024